Usability of two brief questions as a screening tool for domestic violence and effect of #MeToo on prevalence of self-reported violence - Katja Maria Kero; Anne Helena Puuronen; Leo Nyqvist; Ville Lauri Langén (ELSEVIER, 2022)
Objective: Domestic violence is a hidden epidemic. We used a two-question screening tool to explore the prevalence of domestic violence among gynaecological outpatients. We also retrospectively assessed whether there was a change in the prevalence rate of self-reported violence after the launch of the #MeToo movement.Study design: Over an 11-month period, all gynaecological first-time visitors to our outpatient clinic were asked two dichotomous questions that screened for domestic violence and examined whether the violence had an ongoing impact on the respondent's everyday life. We used logistic regression models to assess whether the launch of #MeToo was associated with the answers to these two questions.Results: Of the 6,957 screened women, 154 (2.2 %) tested positive for domestic violence. Among the screen-positive women, 87 (56.5 %) reported that the violence affected their health and well-being. Of these 87 women, 52.9 % wanted further support and 72.4 % had already contacted psychiatric care. Out of all of the patients, the proportion of screen-positive respondents was 2.3 % before and 2.2 % after #MeToo. We did not detect increased odds of self-reporting domestic violence (odds ratio 0.97, 95 % confidence interval 0.70-1.36) or its ongoing impact on the victim's everyday life (odds ratio 1.05, 95 % confidence interval 0.53-2.07) after #MeToo.Conclusions: Our two-question screening tool detected a lower prevalence of domestic violence among gynaecological outpatients than previous reports examining the general population. Our results illustrate the dire challenges in screening for domestic violence that persist even in the post-#MeToo era. Domestic violence remains a highly intimate, stigmatising, and underreported health issue, and systematic measures to screen for and prevent it should be advocated, both in gynaecological patients and the general population. (C) 2020 Elsevier B.V. All rights reserved.